(untitled) (Vietnam Journal of Community Medicine, 2023)
Objective: Describe the results of frozen embryo transfer on day 5, at the fertility center of Hanoi Medical University Hospital in 2021 - 2022. Methods: A cross-sectional descriptive study based on retrospective data of 133 couples who received frozen embryo transfer on day 5, at the fertility center of Hanoi Medical University Hospital in 2021 - 2022. Results: The mean age of the study subjects was 31.0±4.5 years old. The negative rate after embryo transfer was 29.3%. The rate of ectopic pregnancy is 1.5%. The stillbirth rate was 4.5%, during pregnancy was 6.0%, and after birth loss was 0.8%. Preterm birth rate in the study was 9.8% and 42.9% of full-term births. The study’s clinical pregnancy rate after day 5 embryo transfer was 64.7%. 51.1% of the subjects had a single pregnancy, and 12.8% had a twin pregnancy. 70/133 live births in the study, accounting for 52.6%. Conclusion: The clinical pregnancy rate after day 5 embryo transfer at the Medical University hospital is average, the live birth rate is relatively high. This results confirm the good quality of medical and technical services in assisted reproductive technology at the Hospital.